Analytical solutions of the torsional mechanism for a new hybrid fiber-reinforced polymer–aluminum twin-trackway space truss bridge. Issue 12 (December 2016) - Zhang, Dongdong; Li, Feng; Zhao, Qilin; Duan, Yingchang
For emergency purposes, a lightweight space truss bridge was designed. The bridge is composed of twin triangular deck-truss beams incorporating new structural forms and advanced fiber-reinforced polymer profiles. As a new structure, the structural properties of its triangular deck-truss beam have been studied in detail; however, a design-oriented study facilitating the application of the entire twin-trackway bridge under pure torsion remains to be undertaken. The objective of this article is to analytically explore the torsional mechanism of the twin-trackway bridge, which is characterized by torsional angle and torsional stiffness. To verify the derivation procedures and formulae, the pure torsion test and numerical analysis are conducted on a full-scale specimen. The results indicate that the analytical solutions compare well with the experimental and numerical results. The torsional moment is primarily resisted by the vertical bending of twin triangular deck-truss beams. The simplified analytical model can be used with sufficient accuracy for the design of the bridge.